Phosphate uptake kinetics and tissue-specific transporter expression profiles in poplar (Populus × canescens) at different phosphorus availabilities - Kavka, Mareike (BMC Plant Biol, 2016)
BACKGROUND: Phosphorus (P) is a major plant nutrient. It is transported into and allocated inside plants by four families of phosphate transporters (PHT1 to PHT4) with high or low affinity to phosphate. Here, we studied whole-plant P uptake kinetics and expression profiles of members of the PHT families under high, intermediate and low P availability in the woody crop poplar (Populus × canescens) in relation to plant performance. RESULTS: Poplars exhibited strong growth reduction and increased P use efficiency in response to lower P availabilities. The relative P uptake rate increased with intermediate and decreased with low P availability. This decrease was not energy-limited because glucose addition could not rescue the uptake. The maximum P uptake rate was more than 13-times higher in P-starved than in well-supplied poplars. The K(m) for whole-root uptake ranged between 26 μM and 20 μM in poplars with intermediate and low P availability, respectively. In well-supplied plants, only low uptake rate was found. The minimum concentration for net P uptake from the nutrient solution was 1.1 μM. All PHT1 members studied showed significant up-regulation upon P starvation and were higher expressed in roots than leaves, with the exception of PtPHT1;3. PtPHT1;1 and PtPHT1;2 showed root- and P starvation-specific expression. Various members of the PHT2, PHT3 and PHT4 families showed higher expression in leaves than in roots, but were unresponsive to P deprivation. Other members (PtPHT3;1, PtPHT3;2, PtPHT3;6, PtPHT4;6 to PtPHT4;8) exhibited higher expression in roots than in leaves and were in most cases up-regulated in response to P deficiency. CONCLUSIONS: Expression profiles of distinct members of the PHT families, especially those of PHT1 were linked with changes in P uptake and allocation at whole-plant level. The regulation was tissue-specific with lower P responsiveness in leaves than in roots. Uptake efficiency for P increased with decreasing P availability, but could not overcome a threshold of about 1 μM P in the nutrient solution. Because the P concentrations in soil solutions are generally in the lower micro-molar range, even below the apparent K(m)-values, our findings suggest that bare-rooted poplars are prone to suffer from P limitations in most environments. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12870-016-0892-3) contains supplementary material, which is available to authorized users.